FROM OUTLINING TO ACADEMIC WRITING - I Made Wardhana (Jurnal Santiaji Pendidikan (JSP), 2015)
Academic essay writing undergoing the process of pre-writing, drafting, responding, revision, editting and post writing showing that it is not a simple activity, therefore it requires techniques or ways to help the writer, especially a beginner writer in expressing one’s ideas to write an academic writing. This study attempted to find out whether outlining could enhance the efficiency for the students to write an academic essay. The responses to the questionnaires distributed to 115 students showed that outlining could make it easier for them to write academic essay writing especially in organising their ideas.The result of product moment computation also confirmed that there was a very positive correlation between the students’ perception on outlining and their academic essay writing achievement. Therefore, it could be suggested that during the prewriting stage the students should be exposed with the process of writing outline so their writing would be more focussed on the topic idea of the thesis statement and topic ideas of the topic sentences with a good development of ideas and sentences in order to get a unified and coherent writing.